Cisco CCNP data center DCCOR (350-601) - Sequeira, Anthony; Wong, Ronnie (Packt Publishing, 2024)
The course begins with an in-depth look at Cisco's NX-OS, laying a foundation for understanding data center environments. It progresses to OSPFv2 and OSPFv3, crucial for robust network communication, and explores Multi-Protocol BGP and PIM, key for scalable networks. Advanced network solutions like FHRPs, RSTP+, and LACP are covered, essential for network resilience. You'll delve into vPC, VXLAN, EVPN, and OTV, essential for network virtualization and overlay networks. The focus then shifts to Cisco ACI, introducing intent-based networking with Cisco APIC. Topics include ACI Access Policies, Tenant Policies, and Contracts. You'll learn about UCS Rack Servers, Blade Chassis, and delve into UCS Infrastructure and Network Management. The course includes insights on UCS Software Updates, NetFlow, SPAN, and Streaming Telemetry, crucial for network maintenance and troubleshooting. Wrapping up, the course covers Fibre Channel, Port Channels, Nexus Software Updates, and essentials of cloud computing with NIST 800-145, equipping you with the knowledge to handle modern data center demands. What you will learn Understand NX-OS and OSPF protocols Gain expertise in FHRPs and RSTP+ Learn advanced LACP and vPC DCCOR Explore VXLAN and EVPN technologies Grasp ACI Tenant Policies and Contracts Analyze packet flow and cloud concepts Audience This course is ideal for network professionals aiming to specialize in data center technologies. Prior knowledge of networking and basic Cisco concepts is recommended. This course is perfect for those seeking to align their skills with Cisco's advanced data center solutions and practices. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Anthony Sequeira: Anthony Sequeira, CCIE #15626, is a seasoned tech trainer and author with expertise in cloud, cybersecurity, and IT. His IT journey began in 1994 at IBM in Tampa, Florida. He later founded Computer Solutions but discovered his true passion for teaching and writing about technology. In 1996, he joined Mastering Computers, which evolved into KnowledgeNet, where he continued to share the latest tech advancements. Today, he serves as a full-time Edutainer at ACI Learning, delivering global training and authoring textbooks on modern technologies. He holds certifications like CCIE R&S #15626, as well as numerous others from AWS, CompTIA, Juniper, and Microsoft, among others. Anthony's expertise spans the IT landscape. Ronnie Wong: Ronnie Wong has had a diverse career, from diesel service and ministry to computer repair and network administration in small businesses. He set up networks and servers and created policies in these roles. As an Edutainer at ITProTV, now ACI Learning, he started as an IT technical instructor, later working as a contract trainer for the University of Florida, Marion County School Systems, and Nationwide Insurance. He provided Cisco, Microsoft Windows, CompTIA, and IT security training to military and DoD personnel. Now the Director of Content Development at ACI Learning, Ronnie's credentials include CCNP Enterprise Infrastructure, CCNA, CompTIA's A+, Network+, Security+, ISC2 CC, CNA Security, and PCNSA.
Online resource; title from title details screen (O'Reilly, viewed January 23, 2024)
Keywords: Cisco Systems, Inc -- Study guides -- Examinations; Computer networks -- Study guides -- Examinations; Telecommunication -- Study guides -- Switching systems -- Examinations; Réseaux d'ordinateurs; Examens; Guides de l'étudiant; Télécommunications; Systèmes de commutation; Examens; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet